Perbandingan Pola Paes Pengantin Solo Putri Menggunakan Pensil Alis Dan Eyeliner Spidol Pada Kulit Berminyak - Yohanitha Regina Novitasari; Dindy Sinta Megasari; Nieke Andina Wijaya; Dewi Lutfiati (Program Studi Pendidikan Tata Rias, 2026)
Paes is an aesthetic and symbolic element that characterizes traditional bridal makeup, particulary in Solo Putri bridal makeup. In practice, an eyebrow pencil is commonly used to form the paes outline before appliying pidih. However, on oily skin this technique often causes technical problems because the outline tends to fade due to sweet and sebum, wich may cause the pidih to spread beyond the intended pattern. Along with the development of beauty trends, an eyeliner spidol has increasingly bee used as an alternative to create paes pattern formation using an eyebrow pencil and an eyeliner spidol, as well as to analyze the comparison the two cosmetics on oily skin. This study employed a quantitatvie approach with an experimental method. The evaluation was conducted by 3 observers and 27 trained observers using an observation sheet. The ressults showed thar the use of an eyebrow pencil obtained a mean score of 2,77 in the good category, while the eyeliner spidol obtained a mean score of 3,57 in the good category. The Mann-Whitney test indicated a significance value of p<0,005, which means that there is a significant difference between the two cosmetics. Overall, the eyeliner spidol produced paes patterns that were more defined, neater, and more durable on oily skin compared to the eyebrow pencil.